Carbohydrate deficient glycoprotein syndrome type I: ophthalmic aspects in four Sicilian patients. Issue 11 (November 1994) - Fiumara, A; Barone, R; Buttitta, P; Di Pietro, M; Scuderi, A; Nigro, F; Jaeken, J
Abstract : Four patients with carbohydrate deficient glycoprotein (CDG) syndrome type I underwent ophthalmic examination. All of them had retinitis pigmentosa with extinguished scotopic electroretinogram. The importance of CDG syndromes as one of the metabolic causes of retinal dystrophy with 'bony spicule' pigment is stressed.